Social engineering as a component of professional competence in information security of future computer science teachers (Educational Dimension, 2024)
The article considers the actual problem of information security - social engineering. The authors investigate what social engineering is and its main methods, including phishing, vishing, baiting, and pretexting, and analyze the educational programs of the speciality "014.09 Secondary Education (Informatics)" regarding the availability of relevant competencies. The article analyzes data on the components of professional competencies in information security and social engineering of the leading educational institutions of the USA, the EU, and Ukrainian higher education institutions; based on the analyzed data provided in general, the relationship between training in cyber security and social engineering. The authors also explore the role of future computer science teachers in protecting students from the threats of social engineering. They note that a critical factor in this protection is teaching students to recognize and eliminate social engineering threats and how to protect their sensitive information.